Impact of e-government on foreign direct investment in East and Southeast Asia - Huy L VU (Global Business & Finance Review (GBFR), 2023)
Purpose: This empirical study investigates the relationship between e-government and inward foreign direct investment (FDI) in East and Southeast Asia. E-government or electronic government refers to the applications of information and telecommunication technologies to provide public services and information to the citizens. In theory, e-government initiatives may positively influence FDI. Design/methodology/approach: A panel of twelve countries in the region, covering a period between 2003 and 2020, is employed for empirical analysis. Static panel regression methods are applied to estimate the effect of e-government on foreign direct investment of the host countries. Findings: E-government is found to have a positive and statistically significant impact on FDI inflows. This result is robust to heteroskedasticity, autocorrelation, and cross-sectional dependence, and remains consistent under different specifications. Research limitations/implications: E-government initiative is an important and viable channel to attract foreign direct investment to the host countries in the region. Regarding this objective, the countries may concentrate on improving telecommunication infrastructure and online services. Originality/value: This paper is the first empirical attempt to explore the relationship between e-government and foreign direct investment in East and Southeast Asia. It also contributes significantly to the limited empirical studies in the existing literature.
Keywords: 650; Foreign direct investment; E-government development; Location advantages; East and Southeast Asia